Avaliação do impacto de fatores socioeconômicos e da percepção na prevenção do câncer de mama e câncer do colo uterino - Alves, Saionara Açucena Vieira (2018)
Introduction: The association between knowledge about risk factors, symptoms and risk perception with the behavior of women, indicates that awareness plays an important role in cancer prevention. The incidence and mortality rate of breast cancer (CM) and cervical cancer are increasing in Northeast Brazil. There are no Brazilian studies on the effect of risk perception on mammography. There are few studies in the Northeast of Brazil about the socioeconomic factors that affect the achievement of the Breast Examination (BCE). There are no comparative studies among different Brazilian populations, evaluating the effect of socioeconomic factors in the Pap test. Objective: To evaluate the relationship between socioeconomic factors and women's preventive behavior (Mammography, clinical examination of the breasts and Pap smear). Understanding how self-estimation of women's perceived risk, relative to actual risk, affects preventive behavior. Methods: In the present study, 396 women were interviewed at the Francisco Pinto Health Center and at the Municipal Hospital Doctor Edgley in the city of Campina Grande-PB, applying a questionnaire. In all three studies, logistic regression models were applied to identify independent variables that affect women's preventive behavior. Results: The three main socioeconomic variables that affect women's preventive behavior were identified in the three articles. It was investigated how risk perception affects participation in the mammographic screening program, variables that affect the performance of ECM, and compared the performance of the Pap smear test among women from Paraíba and Mato Grosso do Sul. A final logistic regression model indicated that women with low educational level performed the ECM regularly (annual or biennial) 8.48 times less compared to women with high educational level. Those who were not employed had 2.39 and 1.81 less chance of performing ECM at regular intervals. In addition, women who used both services (private and public) had 2.47 and 2.84 times more likely to perform ECM on a regular basis than those who only used the public service. Women between 40 and 49 years of age with low perception of absolute risk and low educational level underwent regular mammographic screening around 2.65 and 2.72 times less compared to those with high-risk perception and high educational level. Education was the only significant variable for women aged 50 years or older who interfered with mammography compliance. Conclusion: Exclusive use of public health services and unemployment were associated with lower adherence to the clinical examination of the breasts. The perception of absolute risk depended on family history. The effect of risk perception on mammography screening was dependent on the age group. Factors such as family history and educational level influenced the adherence to mammographic screening. Unemployment was associated with decreased adhesion to the Pap smear. The low level of education influenced the lower adherence in all the exams (ECM, mammography and Papanicolau). Future programs should focus on targeting women with low educational attainment.